Automatic Generation Control in Low Inertia Power System - MIHOUBI Omar Elfarouk; BEN DJEMAI Hadj Belkacem; ARIF Salem (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electrotechnique, 2022)
The overall system inertia in an interconnected power system may be considerably reduced as a result of a rapid growth in the use of power converter-based Renewable Energy Sources (RESs), increasing the interconnected power system's sensitivity to system instability. This thesis offers an application of Virtual Inertia Control (VIC) in the Automatic Generation Control (AGC) to improve frequency stability of the interconnected power system with high penetration levels of RESs (power system with low-inertia). In this study, MATLAB/Simulink® is used to model the system and simulate the results. A multi-area test system with high RESs penetration level for different circumstances is used to verify the efficiency of the Virtual Inertia Control concept on stability enhancement. Conventional controllers, such as Proportional-Integral-Derivative (PID) controllers, have been proposed to emulate power system inertia using VIC methods.
OPTION: Electrical Power System